Le commerce du coton en Méditerranée a la fin du Moyen Age - Nam, Jong-Kuk, 1968- (Medieval Mediterranean ;, 2007)
Based on a range of medieval commercial documents the author comes to the conclusion that the cotton traffic was one of the motors mobilizing human and material resources on a large scale in the maritime commerce in the Mediterranean in the Later Middle Ages.